2004
DOI: 10.1177/0363546504267050
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanical Testing Device for Measuring Anteroposterior Knee Laxity

Abstract: The Rolimeter is as reproducible and reliable as the KT-1000 arthrometer. It offers a valid method for the measurement of anteroposterior translation in the knee. Higher accuracy was obtained at 20 degrees of flexion for the KT-1000 arthrometer and at 80 degrees of flexion for the Rolimeter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 7 publications
5
70
0
2
Order By: Relevance
“…The present protocol could be useful to the surgeon to decide about additional surgical actions to be taken, [7] 7±2 Langrana [15] 6.8±0.5 Markolf [18] 9±2 7±2 30±8 5±2 12±4 Shoemaker [26] 41±11 47±9 Forster [9] 4.4±1.8 Katabi [14] 4.7±3.6 Boyer [4] 2.4±2.2 Pedowitz [21] 11±2.2 Pollet [22] 4±2.3 Balasch [3] 6.3 Ganko [10] 6.9±1. [15] 11.1±1 Markolf [18] 15±3 9±4 33±8 6±4 14±4 Forster [9] 8.3±3.5 Katabi [14] 8±3 Boyer [4] 6.3±3.1 Pedowitz [21] 21±4 Pollet [22] 6.3±5.4 Balasch [3] 12.7 Ganko [10] 11.4±2.9 Schuster [27] 10(8.9-11.2) 6.4(5.6-7.3) Loh [16] 12 such as lateral plasty in case of a too high laxity is detected after the reconstruction, or a different graft tension. The protocol we have presented, once further validated with a larger set of cases and surgeons, could be easily included in present computer-assisted procedures for ACL reconstruction and, therefore, improve the documentation of ACL procedure at time zero at the intraoperative planning design.…”
Section: Discussionmentioning
confidence: 99%
“…The present protocol could be useful to the surgeon to decide about additional surgical actions to be taken, [7] 7±2 Langrana [15] 6.8±0.5 Markolf [18] 9±2 7±2 30±8 5±2 12±4 Shoemaker [26] 41±11 47±9 Forster [9] 4.4±1.8 Katabi [14] 4.7±3.6 Boyer [4] 2.4±2.2 Pedowitz [21] 11±2.2 Pollet [22] 4±2.3 Balasch [3] 6.3 Ganko [10] 6.9±1. [15] 11.1±1 Markolf [18] 15±3 9±4 33±8 6±4 14±4 Forster [9] 8.3±3.5 Katabi [14] 8±3 Boyer [4] 6.3±3.1 Pedowitz [21] 21±4 Pollet [22] 6.3±5.4 Balasch [3] 12.7 Ganko [10] 11.4±2.9 Schuster [27] 10(8.9-11.2) 6.4(5.6-7.3) Loh [16] 12 such as lateral plasty in case of a too high laxity is detected after the reconstruction, or a different graft tension. The protocol we have presented, once further validated with a larger set of cases and surgeons, could be easily included in present computer-assisted procedures for ACL reconstruction and, therefore, improve the documentation of ACL procedure at time zero at the intraoperative planning design.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have published their results, ranging from 0.24, 0.55-0.72, to 0.49-1.0 [57][58][59]. Again, investigators cited inherent subjectivity in explaining this variability.…”
Section: Rolimetermentioning
confidence: 99%
“…Studies have found comparable results with the KT-1000, Rolimeter, and Stryker devices, and consistently inferior validity and reliability with the Genucom system [36,55,59,60,64,84,85]. It is important to note that each device's results will fundamentally differ, and clinicians must therefore not assume comparability between measurements from different devices [59,60,85].…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Biomechanical evaluation of the knee stability: For the evaluation of knee stability the Rollimeter Aircast™ knee tester was used. Schuster et al [9] have demonstrated that the Rollimeter is as reproducible and reliable as the KT-1000 arthrometer and it offers a valid method for the measurement of anteroposterior translation of the knee. The tests performed were the anterior drawer test and the Lachmann test.…”
Section: Clinical and Objective Evaluations: This Was Done By Anmentioning
confidence: 99%